The Financial Interests of the EU: Implications on the European Rule of Law Idea - Francesco Bilancia (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1096-1112 | Article | (Table of Contents) I. Introduction. – II. Starting from the end: the Rule of Law conditionality mechanism. – III. Rule of law, mutual trust, and the macroeconomic dimension. – IV. The EU Rule of Law as an instrument of political dominance. – V. Some provisional conclusions. | (Abstract) This Article examines the significance of the Rule of Law as a common value in the European Union, focusing especially on the decisions of the European Court of Justice concerning the EU Conditionality Regulation. It considers the role of mutual trust among Member States in fostering an ever-closer union and investigates the so-called “macroeconomic dimension” of the EU Rule of Law. The Article concludes that the EU Rule of Law should not be understood as a tool for asserting political dominance by EU institutions or for expanding Union-conferred legal competencies beyond the limits established by the Treaties.